Be sweet to babies during painful procedures: Evaluation of a parent-targeted and mediated video in Farsi. Issue 6 (December 2021) - Modanloo, Shokoufeh; Hu, Jiale; Reszel, Jessica; Larocque, Catherine; Harrison, Denise
Abstract: Newborn screening is necessary for early detection of rare diseases, however, venipuncture and heel lance are painful for newborn infants. There are however effective evidence-based pain management strategies include breastfeeding or skin-to-skin care or giving a small volume of sweet solution. These strategies are demonstrated in a parent-targeted publicly accessible video titled Be Sweet to Babies, which has been produced and disseminated in multiple languages, including Farsi. We aimed to evaluate (1) the dissemination and reach of the Farsi video (using video analytics); and (2) viewers' i) baseline knowledge and previous use of these pain management strategies; ii) intention to advocate for/recommend these strategies (using an online survey accessed from the video). Eight months after the release date, the video had 618, 685 views and 202 viewers completed the survey. Almost half the participants knew about or used breastfeeding (n = 81, 40%), skin-to-skin care (n = 106, 53%) or sucrose (82, 41%) before viewing the video. After viewing the video, almost all participants (n = 195, 96%) intended to advocate for use or recommend these strategies to others. This study showed the acceptability, reach, and feasibility of the "Be Sweet to Babies" video, translated and voiced over in Farsi, as a parent-targeted and mediated knowledge translation tool.